Pameran Sejarah Sebagai Wadah Edupreneurship Mahasiswa Dalam Inovasi Karya Berbasis Sejarah Lokal Dan Potensi Wisata - Walarif, Ilham; Fitra Widya Wati; Khaeruddin; Oschar Sumardin; Irwandi (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2025)
This service activity is motivated by students' low understanding of the packaging of historical content into educational products with economic value, and the non-optimal integration of entrepreneurial values in history learning. The purpose of this activity is to foster the entrepreneurial spirit of students through edupreneurship developed in the form of local history-based exhibitions. The method used is a Participatory Action Research (PAR) approach that involves students as active subjects in training, production, and marketing of historical products, as well as organizing exhibition activities. The activity began with training on basic edupreneur concepts, product packaging, and marketing strategies. The activity featured a variety of creative products such as traditional snacks, replicas of pinisi ships, and souvenirs with local history motifs. This activity succeeded in increasing students' capacity to think critically, innovate, and work together productively. The entrepreneurship talk show held at the same time also strengthened students' motivation and entrepreneurial insights. The results of the activity show that the history exhibition is effective as a medium for transforming contextual, applicable, and economically valuable history learning through an edupreneurship approach.